EFFICACY OF ETANERCEPT IN CHILD WITH SEVERE POLYARTICULAR TYPE OF JUVENILE RHEUMATOID ARTHRITIS - T.M. Bzarova; Ye.I. Alexeeva; S.I. Valieva; N.A. Tsurikova; E.G. Chistyakova; K.B. Isaeva; R.V. Denisova; T.V. Sleptsova; E.V. Mitenko (Вопросы современной педиатрии, 2011)
The article presents a case report of severe and prolonged polyarticular rheumatoid arthritis resistant to the treatment with classic immunosuppressive agents, nonsteroidal anti-inflammatory drugs and corticosteroids. Authors describe successful treatment with soluble receptors to TNF _ — etanercept 0.4 mg for 1 kg of body weight during 36 weeks. Pain and exudative inflammation in joints lessened and the range of motions in joints increased in 4 weeks after the beginning of treatment. 9 months of treatment significantly increased the quality of life of a child and parents.Key words: children, juvenile rheumatoid arthritis, etanercept.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (2): 184–192)